2017
DOI: 10.1111/jomf.12404
|View full text |Cite
|
Sign up to set email alerts
|

Who Helps Single Mothers in Nairobi? The Role of Kin Support

Abstract: Single mothers often turn to their extended kin for financial assistance and to help with child care. Such support may be especially important in areas of high poverty and poor environmental conditions. Using novel kinship data, this paper assesses the extent of support given by over 3,000 relatives to 462 single mothers living in a slum area of Nairobi, Kenya. Contrary to stereotypes about families in sub-Saharan Africa, the active kin network of single mothers is relatively small and nearly a fifth of mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 43 publications
3
52
1
Order By: Relevance
“…In a few countries, we also observed that the timing of a second premarital birth is lower among younger women, those in rural areas, and women who are not literate. This finding contrasts with our hypothesis, considering that lower levels of education and high levels of unemployment place many single mothers in precarious positions, struggling to pay for food, and other necessities critical for the health and well-being of themselves and their first child [18]. Although understanding why single mothers have a second premarital birth despite its associated negative consequences is beyond the scope of this study, one plausible explanation is that socioeconomically disadvantaged single mothers may have low negotiating power and lack access to modern contraceptive methods that could help minimize the risk of a second birth [42,44,45].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In a few countries, we also observed that the timing of a second premarital birth is lower among younger women, those in rural areas, and women who are not literate. This finding contrasts with our hypothesis, considering that lower levels of education and high levels of unemployment place many single mothers in precarious positions, struggling to pay for food, and other necessities critical for the health and well-being of themselves and their first child [18]. Although understanding why single mothers have a second premarital birth despite its associated negative consequences is beyond the scope of this study, one plausible explanation is that socioeconomically disadvantaged single mothers may have low negotiating power and lack access to modern contraceptive methods that could help minimize the risk of a second birth [42,44,45].…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, in some communities, the socio-economic development of such women with regards to education and accessibility to job opportunities may be restrained [12][13][14][15]. They also tend to have higher poverty rates, fewer economic resources than married mothers, and less support from families [16][17][18]. Recent evidence also suggests that having a premarital birth may affect women's marriageability in African countries [5,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a small, but growing, body of research shows that these unmarried mothers (regardless of age) find it harder to find a spouse (Smith‐Greenaway and Clark ) and face discrimination when seeking maternal care (Gage ). Older single mothers are also less likely than younger ones to receive help from family members (Clark et al. forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…Even in places where single motherhood carries little social stigma, unmarried mothers may struggle to simultaneously care for their young children and secure sufficient economic resources to pay for their food, clothes, housing, and health care. Although other family members may step in to help never‐married single mothers, in some contexts support from extended kin for single mothers is quite limited (Clark et al. forthcoming).…”
Section: Implications Of Premarital Fertility In Sub‐saharan Africamentioning
confidence: 99%
“…Second, Agincourt HDSS data and the social connections database allow us to measure the effects of non-coresident kin who do not live with a child but may nonetheless play a critical role in providing material support. Recent studies have questioned the limitations of the household as an organizing concept for measuring kinship support (Clark et al 2017; Madhavan et al 2017), and so future work ought to address whether kin outside the household increase explanatory power in similar modelling strategies. Third, further refinements of the analysis presented here are possible.…”
Section: Discussionmentioning
confidence: 99%